Systematic characterization and proposed pathway of tetracycline degradation in solid waste treatment by Hermetia illucens with intestinal microbiota. (November 2018) - Cai, Minmin; Ma, Shiteng; Hu, Ruiqi; Tomberlin, Jeffery K.; Yu, Chan; Huang, Yongping; Zhan, Shuai; Li, Wu; Zheng, Longyu; Yu, Ziniu; Zhang, Jibin
Abstract: Antibiotics can effectively protect livestock from pathogen infection, but residual antibiotics in manure bring risks to ecosystems and public health. Here, we demonstrated that black soldier fly larvae (BSFL) could provide an environmentally friendly manure treatment based on their ability to effectively and rapidly degrade tetracycline (TC). Investigation of the biological mechanisms and degradation pathways of TC by BSFL indicated that nearly 97% of TC was degraded within 12 days in a non-sterile BSFL treatment system, which is up to 1.6-fold faster than that achieved by normal composting. Our results showed that rapid TC-degradation was largely carried out by the intestinal microbiota of the larvae, which doubled the TC-degradation rates compared to those achieved in sterile BSFL systems. This conclusion was further supported by highly-efficient TC-biodegradation both in vivo and in vitro by four larval intestinal isolates. Moreover, detailed microbiome analysis indicated that intestinal bacterial and fungal communities were modified along with significantly increased tet gene copy number in the gut, providing the means to tolerate and degrade TC. Through analysis of TC degradation in vitro, four possible biodegradation products, two hydrolysis products and three conceivable inactivation products were identified, which suggested TC degradation reactions including hydrolysis, oxygenation, deamination, demethylation, ring-cleavage, modification, etc. In conclusion, our studies suggested an estimation of the fate of TC antibiotics in manure treatment by BSFL colonized by gut microbes. These results may provide a strategy for accelerating the degradation of antibiotics by adjusting the intestinal microbiota of BSFL. Graphical abstract: Image 1 Highlights: BSFL degraded tetracycline (TC) more effectively than normal composting. Synergistic effect of BSFL with intestinal microbiota accelerated TC-degradation. Intestinal microbial communities were modified along with increased tet genes. Identified products exhibited the ring-cleavage pathway of TC-biodegradation. Proposed pathways of hydrolysis, biodegradation and inactivation were conjectured.